Nanoparticle for delivery of antisense γPNA oligomers targeting CCR5 - Bahal, Raman (Landes Bioscience, 2013)
The development of a new class of peptide nucleic acids (PNAs), i.e., gamma PNAs (γPNAs), creates the need for a general and effective method for its delivery into cells for regulating gene expression in mammalian cells. Here we report the antisense activity of a recently developed hydrophilic and biocompatible diethylene glycol (miniPEG)-based gamma peptide nucleic acid called (MP)γPNAs via its delivery by poly(lactide-co-glycolide) (PLGA)-based nanoparticle system. We show that (MP)γPNA oligomers designed to bind to the selective region of Chemokine Receptor 5 (CCR5) transcript, induce potent and sequence-specific antisense effects as compared with regular PNA oligomers. In addition, PLGA nanoparticle delivery of (MP)γPNAs is not toxic to the cells. The findings reported in this study provide a combination of γPNA technology and PLGA-based nanoparticle delivery method for regulating gene expression in live cells via the antisense mechanism.